2013
DOI: 10.1080/19424280.2012.693543
|View full text |Cite
|
Sign up to set email alerts
|

The influence of barefoot and barefoot-inspired footwear on the kinetics and kinematics of running in comparison to conventional running shoes

Abstract: Jane (2012) The influence of barefoot and barefoot inspired footwear on the kinetics and kinematics of running in comparison to conventional running shoes. Footwear Science, 5 (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
84
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 20 publications
8
84
1
Order By: Relevance
“…Three-dimensional positions of each marker were captured by eight digital infrared cameras (BTS® Smart-E, BTS Bioengineering, Milan, Italy) sampling at 120 Hz. After assessing the frequency at which 95% of the signal power was below, the signals were filtered using a lowpass fourth-order zero-lag Butterworth filter with a cut-off frequency of 10 Hz (Sinclair et al, 2013). Marker positions were processed to estimate a number of variables (Figure 1), including: the knee angle and the foot angle at ground contact with respect to the horizontal, the peak knee flexion angle during stance, the knee flexion range of motion (ROM) during stance, the stride angle (i.e.…”
Section: Data Collection and Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Three-dimensional positions of each marker were captured by eight digital infrared cameras (BTS® Smart-E, BTS Bioengineering, Milan, Italy) sampling at 120 Hz. After assessing the frequency at which 95% of the signal power was below, the signals were filtered using a lowpass fourth-order zero-lag Butterworth filter with a cut-off frequency of 10 Hz (Sinclair et al, 2013). Marker positions were processed to estimate a number of variables (Figure 1), including: the knee angle and the foot angle at ground contact with respect to the horizontal, the peak knee flexion angle during stance, the knee flexion range of motion (ROM) during stance, the stride angle (i.e.…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…In contrast to Squadrone and Gallozzi (2009) and Paquette et al (2013), they concluded that minimalist and lightweight shoes do not change the biomechanics of highly trained runners in comparison with more conventional shoes. Finally, Sinclair, Greenhalgh, Brooks, Edmundson, and Hobbs (2013) found significant differences between barefoot running and running in a minimalist shoe and concluded that the mechanics of shoes that aim to simulate barefoot movements does not mimic barefoot locomotion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accelerometer was attached onto a piece of lightweight carbon-fibre material using the protocol outlined by Sinclair et al [25], and strapped securely to the distal anterio-medial aspect of the tibia in alignment with its longitudinal axis 0.08 m above the medial malleolus [26].…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers reported that barefoot running results in reduction of chronic injuries in runners [4]. This can be due to the fact that in barefoot running, heel-toe pattern is used, which leads to reduction of contact forces on organs from ground or land surface [5].…”
Section: Introductionmentioning
confidence: 99%